Correlação entre marcadores salivares inflamatórios e fatores psicossociais em pacientes com deformidades dentofaciais - Volkweis, Maria Carolina Carvalho (2020)
The skeletal discrepancies between the dental arches that cannot be corrected by orthodontic treatment are known as dentofacial deformities (DD). Orthognathic surgery (OS) is considered the ideal treatment for those skeletal discrepancies. This study aimed to evaluate the quality of life and psychological symptoms in patients with DD pre-operatively, correlating these parameters with the salivary levels of cytokines and metabolites of the kynurenine pathway. The research protocol was submitted and approved by the institutional Ethics Committee (3.343.197). The sample consisted of thirty-six patients (15-48 years), divided into two groups: control (orthodontic treatment; n=19) and test (DD, before OS; n=17). Quality of life was assessed using two questionnaires: (i) World Health Organization Quality of Life BREF (WHOQOL-BREF), and, (ii) Orthognathic Quality of Life Questionnaire (OQLQ). The symptoms of depression, anxiety and stress were assessed using the Depression, Anxiety, and Stress Scale-21 (DASS-21). In addition, patients were evaluated by using the Satisfaction with Life Scale and the Rosenberg Self-Esteem Scale. The levels of pro-inflammatory cytokines, interleukin-1β (IL-1β) and interleukin-6 (IL-6), or the anti-inflammatory cytokine, interleukin-10 (IL-10), were determined by ELISA, through the collection of stimulated total saliva. The salivary levels of glutamate and the kynurenine pathway metabolites, namely kynurenic acid, quinolinic acid, and kynurenine, were measured by high-performance liquid chromatography coupled to mass spectrometry (LC-MS/MS). For statistical analysis, Student's t-test, or two-way ANOVA followed by Sidak's post hoc test, were used. Frequency data were assessed using the Chi-square test. Pearson's correlation coefficient was applied to assess the possible correlation between the results of the instrument scores, and the biochemical data. P values less than 0.05 were considered as indicative of significance. The results of the general quality of life assessment, measured by the WHOQOL-BREF, did not show statistical differences between the control and test groups. However, the analysis of question 1 of this instrument showed a P-value = 0.06, according to the comparison of the control and test groups, suggesting a poorer overall quality of life in individuals with DD. The parameters evaluated by the Satisfaction with Life scale, Rosenberg Self-Esteem Scale and DASS-21 did not reveal any significant differences between the groups. However, the results of the OQLQ, specific for the assessment of patients with DD, showed a significant difference, either for the general scores or the specific domains. The test group had poorer quality of life compared with the control group, mainly in relation to social aspects, facial esthetics, and oral function. The levels of IL-1β and glutamate were higher in patients with DD. Conversely, there was no significant difference in the salivary levels of the metabolites of the kynurenine pathway. A positive correlation was observed between salivary glutamate levels and the scores of the oral function domain, from the OQLQ instrument. This study showed for the first time that patients in the preoperative period of OS have high levels of inflammatory biomarkers, such as IL-1β and glutamate, which might be associated with poorer DD-related quality of life scores. Our data opens new perspectives for understanding and improving the care for patients with DD.